Best Out of Waste: A Review on Solid Waste - Inamdar, Amol A. (International Journal For Research In Mechanical & Civil Engineering, 2017)
Today world is suffered by some major problems. Production of waste is one of them. Waste is nothing but the matters, which are useful in past but, useless in present. These waste can made useful again by adopting some developed techniques like recycling. This can help us to prevent the production of waste and thereby further future problems. It can also help in production of some useful materials like energy production, economy of a country, good environment etc. Getting best out of waste can be done on individual as well as on commercial basis. The materials like steel, paper, aluminum, glass, plastic etc. which are termed as waste after its purpose is over, can further be used for same or different purpose by practicing three Rs i.e. Reduce, Reuse and Recycle. This results in good environment, economy and thereby a good, developed community. This also solves the problem of space for land filling. “If I have one dollar and you have one dollar, and you give me one dollar and I give you one dollar, we will both have one dollar”. However, “if I have one idea and you have one idea, and you tell me yours and I tell you mine, we will both have two ideas.” That is the principle behind getting “BEST OUT OF WASTE”. This paper is trying to cover the ways for getting “BEST OUT OF WASTE”.